Consensus statement on injury definitions and data collection procedures for studies of injuries in rugby union. Issue 5 (23rd April 2007) - Fuller, Colin W; Molloy, Michael G; Bagate, Christian; Bahr, Roald; Brooks, John H M; Donson, Hilton; Kemp, Simon P T; McCrory, Paul; McIntosh, Andrew S; Meeuwisse, Willem H; Quarrie, Kenneth L; Raftery, Martin; et al.
Abstract : Wide variations in the definitions and methodologies used for studies of injuries in rugby union have created inconsistencies in reported data and made interstudy comparisons of results difficult. The International Rugby Board established a Rugby Injury Consensus Group (RICG) to reach an agreement on the appropriate definitions and methodologies to standardise the recording of injuries and reporting of studies in rugby union. The RICG reviewed the consensus definitions and methodologies previously published for football (soccer) at a meeting in Dublin in order to assess their suitability for and application to rugby union. Following this meeting, iterative draft statements were prepared and circulated to members of the RICG for comment; a follow-up meeting was arranged in Dublin, at which time all definitions and procedures were finalised. At this stage, all authors confirmed their agreement with the consensus statement. The agreed document was presented to and approved by the International Rugby Board Council. Agreement was reached on definitions for injury, recurrent injury, non-fatal catastrophic injury, and training and match exposures, together with criteria for classifying injuries in terms of severity, location, type, diagnosis and causation. The definitions and methodology presented in this consensus statement for rugby union are similar to those proposed for football. Adoption of the proposals presented in this consensus statement should ensure that more consistent and comparable results will be obtained from studies of injuries within rugby union.